2010
DOI: 10.3923/pjbs.2010.287.292
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Delayed Repair and Nerve Grafting for Treatment of Cut Median and Ulnar Nerves

Abstract: Traumatic cutting of peripheral nerves of median and ulnar in forearm and wrist can cause disablating sensory and motor disorders in patients' hands. We conducted the present study to compare the results of three surgical methods for repair of injured median and ulnar nerves. We studied 85 patients aged 12-59 years (average, 34 +/- 18 years) with 105 cut median and ulnar nerves at forearm and wrist presenting to Tabriz Shohada hospital from 1994 to 2003. The patients followed for 2-10 years. Sixty patients (65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…In 2010, Mohseni et al in Iran reported that early primary repairs have the best results with all 60 patients showing some recovery and 25/65 (38 %) having excellent results, compared to poor recovery and 7/25 (28 %) failures with delayed primary repair and 5/15 (33 %) failures after delayed nerve graft [231]. In 2014, George and Boyce reviewed 28 studies (1577) of peroneal nerve repairs [111].…”
Section: Autologous Repairs and Timingmentioning
confidence: 99%
“…erefore, considering a 50% regeneration rate in the proximal and distal repair sites and the cross-sectional area ratio of the two nerves, the estimated success rate is only 13%. In a comparative study of primary repair, delayed repair, and nerve graft, good to excellent results were achieved in 78% of the primary repair group but only 33.3% of the nerve graft group [22]. Similarly, in another study comparing microsuture, interpositional nerve graft, and laser solder weld repair of the rat inferior alveolar nerve, interpositional nerve graft was the least effective [23].…”
Section: Discussionmentioning
confidence: 97%